The prophecy of Ezekiel the glory of the Lord - Feinberg, Charles Lee (Chicago, IL Moody, 1969)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Bible. O.T. Ezekiel. Apocalyptic passages -- commentaries